Minimally Invasive Fundoplication is Safe and Effective in Patients with Severe Esophageal Hypomotility. Issue 6 (November 2016) - Goldberg, Michael B.; Abbas, Abbas El-Sayed; Smith, Michael S.; Parkman, Henry P.; Schey, Ron; Dempsey, Daniel T.
Objective: Fundoplication is used to treat refractory gastroesophageal reflux disease (GERD). A subset of patients has coexisting esophageal dysmotility, including aperistalsis or hypoperistalsis. These patients may be at increased risk of dysphagia after fundoplication. To evaluate the outcomes of minimally invasive fundoplication (MIF) in patients with GERD and esophageal hypomotility. Methods: Retrospective review of all patients who underwent MIF and had severe esophageal hypomotility from January 2003 to June 2013. Patients underwent both pH testing and high-resolution esophageal manometry before surgery, in addition to symptom assessment before and after surgery. Severe esophageal hypomotility was defined as mean distal amplitude of contraction of less than 30 mm Hg and liquid bolus clearance of less than 50%. Results: Thirty-four patients with GERD and esophageal hypomotility were included. By manometry, 38% had scleroderma-like esophagus and the other 62% had ineffective peristalsis. Ten patients (29%) had systemic scleroderma. Fundoplications performed (34 laparoscopically and 4 robotically) included Toupet (30), Dor (2), and Nissen (2). All patients tolerated oral feeding at a median of 1 day. One patient required surgical revision at 4 months postoperatively. Mean follow-up was 36 weeks, at which time 41% were asymptomatic and 56% had reduced symptoms. Persistent dysphagia was noted in four patients (11.7%) and was successfully treated with endoscopic dilation. Conclusions: Minimally invasive fundoplication is both safe and effective in treating patients with severe GERD and concomitant esophageal hypomotility. Those with postoperative dysphagia are successfully managed by endoscopic treatments.